Key performance indicator disclosure through the internet: towards an integrated scoreboard - Lopes, I. T. (Journal of Social Technologies, 2014)
Purpose – Information disclosure is driven by multiple determinants, most of them supported by traditional theories, such as agency theory, contingency theory, and legitemacy theory. This research aims to identify a set of Key Performance Indicators (KPI), disclosed to stakeholders through Internet. It also aims to apply for an integrated performance scorebord, acting it as a dynamic comparative tool, in particular for listed companies which market value is driven by investors expectations and needs. Design/methodology/approach – Based on 47 listed companies from the Portuguese Stock Index regulated market, and through an interpretive content analysis, research was driven towards the identification of KPI that were explicitly reported to stakeholders through structured or unstructured frameworks. This qualitative approach supports the evidences about performance indicators reported by listed companies to stakeholders, in particular to potential stockholders. Findings – Companies disclose a wide variety of key performance indicators, however in most cases included in their periodical management reports. Only a low number of companies disclose those indicators through a visible form in their web sites. Furthermore, KPI disclosed have a generic nature and are usually complemented by theoretical explanations about their evolution and trends. The diversity of indicators disclosed does not permit a comparision between companies and activity sectors. Key performence indicators are still disclosed on a voluntarily basis, remaining, in this scope, multiple agency conflicts and other issues around agency costs. Altough the intensity and categorization in the information disclosure, a standard framework is required in orther to ensure a dynamic comparision between companies or sectors. Research limitations – The scope of this research is the Portuguese regulated market. Further research can introduce in the sample companies listed in other European regulated markets or even non listed companies. The indicators selection for the proposed framework was based exclusively on frequencies and not on the value and importance attributed by stakeholders to them. Thus, a survey is required in order to certify that indicators selected are the ones that best fit with stakeholders’ expectations and needs. Furthermore, the research was based on web sites content and management reports analysis which introduces in the analysis a certain level of subjectivity, natural source of interpretations’ biases. Practical implications – Empirical evidence is the basis for a structured KPI scoreboard proposal in order to ensure a periodical comparision between companies, from the perspective of external stakeholders. Originality/value – This paper grants and promotes an integrated overview about the key performance indicators expressly disclosed to stakeholders through Internet by Portuguese listed companies. This evidence has used as a basis for a scorboard proposal towards a comparative analysis in the traditional balanced scorecard perspectives. This scoreboard can be disclosed to market by companies as a basis for an overall performance evaluation and business comprehensiveness. However, further developments are required, in particular in the domain of policy making. Information disclosed to market is not enough regulated in order to minimize the performance analysis discretion and overall transparency.